MIMO processing for 4G and beyond : fundamentals and evolution - Silva, Mario Marques da; Monteiro, Francisco A. (CRC Press, 2014)
"Multiple-input multiple-output was from the beginning a disruptive idea which opened horizons to up-until-then unimaginable data rates and system capacities in wireless systems. This book offers a fresh look at MIMO signal processing, namely its detection (including in the frequency domain) and precoding. It also looks at its combination with OFDM, UWB and CDMA and the impact at the system-level. MIMO remains a pillar of high-speed systems beyond 4G which incorporate massive MIMO and network coding at the physical layer and these topics are also addressed. The book brings together some highly cited authors from first-class institutions."--